High spectral and spatial resolution MRI of age related changes in murine prostate - Foxley, Sean (Magn Reson Med, 2008)
The purpose of this work was to evaluate high resolution echo-planar spectroscopic magnetic resonance imaging of normal and pre-cancerous prostatic changes in a transgenic mouse line. Simian virus large T-antigen transgenic male mice (n = 7, age = 34 ± 3.7 weeks) with prostatic hyperplasia and intraepithelial neoplasia (PIN) were studied. High spectral and spatial resolution (HiSS) MRI of the water proton signal was compared to the FID integral image and conventional gradient echo and spin echo imaging. Water peak-height images of the prostate produced from HiSS datasets showed improved contrast-to-noise ratio (p < 0.03), and greater morphological detail (p < 0.004) based on texture analysis. Despite the high spectral resolution of the HiSS datasets, signal-to-noise ratio compared favorably with that of the FID integral and conventional images. Lobular features in HiSS images of older mice were consistent with hyperplasia seen on histology. A partially deuterated water-filled catheter was inserted in the mouse rectum for susceptibility matching between the colon interior and exterior to minimize image artifacts. These preliminary results suggest that HiSS MRI provides detailed morphology of the murine prostate and can detect early changes associated with the development of cancer. HiSS MRI of patients may have similar advantages.